Culture, power and the role of intellectuals: The dilemma of the field battle (Polis (Santiago), 2018)
The following article confines itself to the dilemmas that the professional experiences, the intellectual who positions himself into a trench of knowledge that has common cause with the clash of the current economic-social model. This work also analyzes the struggle that exists between the satisfaction of the needs of the institution where he works, and those explicit and latent needs of the human group where he materializes his disciplinary exercise. The purpose, then, is to sum oneself to the social project that calls to field militancy, to the resignificance of the intellectual commitment with the oppressed class, to the struggle that intellectuals must give in the field, not only against the symbolic power, but against neoliberal reason.
Keywords: subjectivation technologies; cultural field; biopower